A Capability Approach de Amartya Sen e o indicador de desenvolvimento humano (IDH) - Bomfim, Marianna Percinio Moreira (2012)
This dissertation aims to introduce the components of the economic theory of well-being proposed by Sen, called capability approach, and to discuss its influence on the human development index (HDI) - an indicator of well being presented in the annual reports of the United Nations Development Programme (UNDP).To that effect, firstly the methodological path done by Sen in the elaboration of his approach is presented. To do so, the author retake the thoughts of Adam Smith, analyses the economic theory of well-being and its utilitarian foundations and uses concepts present on Kenneth Arrow s and John Rawls works. Then, the reviews made regard the income and GDP when used as indicators of human development are listed, backing the creation of HDI as an alternative to a less restrictive measure. Besides the concept of human development that supports the indicator, it is presented: the calculation process developed from 1990, some criticisms and suggestions suffered in the last twenty years and the construction of a new HDI in 2010.In conclusion, we discuss the influence of Sen s approach in the UNDP indicator, beyond the limitations of the analyzes of well-being, given that existing tools can not capture all dimensions of human development presented in the theory, inferring that, regard the great progress made on the human condition evaluation due to today, it is still necessary theoretical and technical improvement for a broader understanding of people s well-being